Statistical modeling of phenotypic, pedigree and genomic information for improved genetic evaluation in modern plant breeding : a case study with sorghum - Velazco, Julio Gabriel (2020)
Tesis para obtener el grado de Doctor of Philosophy, de la Wageningen University, en marzo de 2020